Copper complex with sulfamethazine and 2,2′-bipyridine supported on mesoporous silica microspheres improves its antitumor action toward human osteosarcoma cells: cyto- and genotoxic effects - Cadavid Vargas, Juan Fernando (2019)
Ideal drugs to cure cancer leave normal cells unharmed while selectively turning tumor cells unviable. Several copper complexes have been able to selectively slow down tumor proliferation. We hypothesized that Cu(smz)2(bipy)·H2O (1)—a copper-complex that has two ligands capable of interacting with DNA—would outperform Cu(smz)2(OH2)·2H2O (2), and also that supporting 1 on mesoporous silica spheres would decrease even further tumor cell viability in vitro. After exposing osteosarcoma cells (MG-63) and normal phenotype cells of bone origin (MC3T3-E1) to either complex, we studied their toxic effect and mechanisms of action. We determined cell viability (MTT assay) and quantified formation of reactive oxygen species (oxidation of DHR-123 to rhodamine). Moreover, we assessed genotoxicity from (i) formation of micronucleus (MN assay) and (ii) damage of DNA (Comet assay). After the exposure of 1 supported on silica spheres, we tested cell viability. Our results confirm our hypotheses: inhibition of tumor cells follows: supported 1 > dissolved 1 > 2. Future work that enhances the load of the complex exclusively in mesopores may improve the ability of 1 to further inhibit tumor cell viability.